The Supreme Macaroni Company [large type] : a novel - Trigiani, Adriana (Valentine trilogy, 2013)
When a secret about her business partner and lover is revealed during her family's celebration of The Feast of the Seven Fishes, Valentine Roncalli must make life-altering choices as she fights for everything she wants while sustaining her family's business and enjoying life to the fullest.